Develpoment of Four Tier Multiple Choice Diagnostic Test Instrument to Detect Misconception on Chemical Bonding - Febriana Sari, Hilmalia; Agustini, Rudiana (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2024)
Misconception is a concept that is not in accordance with scientific understanding which contradicts the concept that has been believed to be true by experts. Misconceptions in students will occur continuously if not given the right treatment. The treatment given to students can be done well if misconception detection is carried out on students. Misconceptions that are not detected by the teacher can hinder students in receiving further learning. Diagnostic tests can be used to detect misconceptions in students. This study aims to determine the feasibility of a four-tier multiple choice diagnostic instrument to detect students' misconceptions on chemical bonding material based on validity and reliability aspects. The validity of the four-tier multiple choice diagnostic instrument was assessed by three validators based on content, construct, and language criteria using a 1-5 Likert scale calculation. The reliability of the four-tier multiple choice diagnostic instrument is calculated using the Cronbach Alpha equation. Based on the results of the study, it can be concluded that (1) Content validity, construct validity, and language validity have consecutive mode values of 5, 5, and 4 with an overall mode value of 5 so that it is included in the very valid criteria. (2) The instrument developed is declared reliable with the value of the results of rcount> rtable with details of the reliability coefficient on the instrument (rcount) of 0.381 and the rtable value used is 0.373. The diagnostic test instrument that has been developed is declared suitable for use.